2010
DOI: 10.4314/ajfand.v10i8.60895
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, physicochemical and functional properties of lupin (<i>Lupinus albus</i>) seeds grown in Ethiopia

Abstract: White lupin (Lupinus albus) seeds collected from the local markets of Debretabor (DT) and Dembecha (DB) in Ethiopia were studied for their chemical composition, physicochemical and functional properties. Moisture, total ash, crude protein, crude fat, crude fiber and minerals were determined. Mean values for protein, crude fat, total carbohydrates, crude fiber, and crude ash content of the two samples were 40.22, 8.92, 47.73, 10.08 and 3.15 g/100g, respectively on dry weight basis. The mean values of minerals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 19 publications
8
33
2
Order By: Relevance
“…Different reactions of L. albus and L. luteus to the extracts were probably determined by different chemical composition of their seeds and their physicochemical properties (seed weight, bulk density, volume, water absorption, seed coat content, etc.). A similar study had been performed on L. albus (Tizazu & Emire, 2010) but there was no data and comparison with L. luteus.…”
Section: Resultsmentioning
confidence: 99%
“…Different reactions of L. albus and L. luteus to the extracts were probably determined by different chemical composition of their seeds and their physicochemical properties (seed weight, bulk density, volume, water absorption, seed coat content, etc.). A similar study had been performed on L. albus (Tizazu & Emire, 2010) but there was no data and comparison with L. luteus.…”
Section: Resultsmentioning
confidence: 99%
“…Boschin et al (2008) in the field trial with six white lupin cultivars in two locations indicated, that variance of genotypic effects was much larger than genotype-environment interaction for oil content and fatty acid composition. Above mentioned factors can explain differentiated results of fat content in seed of white lupin (5.9, 7.6, 8.9, 9.4, 9.6, 9.7, 10.7, 10.9 and 14.6% obtained by following authors respectively: Erbas et al 2005;Roth-Maier and Kirchgessner 1993;Tizazu and Emire 2010;Petterson et al 1997;Green and Oram 1983;Jansen 2006;Uzun et al 2007;Rybinski et al 2015;Martinez-Villaluenga et al 2006). It was also shown for yellow lupin that seed development was accompanied by an increase of oil content from 4.45% in 30th day after flowering to 5.57% in 55th day after flowering (Adomas and Piotrowicz-Cieślak 2010).…”
Section: Fat Content and Fatty Acid Compositionmentioning
confidence: 99%
“…In most Fabaceae plants the content of crude fibre ranges from 8% to 27.5%, and that of soluble fibre from 3.3% to 13.8% (Guillon & Champ 2002). The average content of total fibre is from 101 g/kg (Tizazu & Emire 2010) to 367 g/kg (MartinezVillaluenga et al 2006) (Table 4).…”
Section: Basic Seed Composition and Properties Of Its Constituentsmentioning
confidence: 99%